2024
DOI: 10.1186/s13102-024-00842-4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of strategic napping on peak expiratory flow and respiratory function in young elite athletes

Ahmet Kurtoğlu,
Özgür Eken,
Engin Aydın
et al.

Abstract: Respiratory health is a critical determinant of athletic performance, and the utilization of restorative strategies, such as strategic napping, may offer a competitive edge to athletes. This study investigates the effects of nap duration on the respiratory function of young elite athletes who have achieved top rankings national competitions. Participants engage in three test sessions with varying nap durations: no nap (N0), a 25-minute nap (N25), and a 45-minute nap (N45), with a minimum 72-hour interval betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…The research underscores the significance of PFR in sports performance, particularly in activities requiring endurance and efficient breathing. Studies have consistently shown that higher PFR values, indicative of superior respiratory function, directly correlate with enhanced athletic abilities (Mackała et al, 2019;Kurtoğlu et al, 2024;Lydia & Latha, 2019). Furthermore, yoga has emerged as a promising avenue for improving PFR and overall lung function.…”
Section: Introductionmentioning
confidence: 99%
“…The research underscores the significance of PFR in sports performance, particularly in activities requiring endurance and efficient breathing. Studies have consistently shown that higher PFR values, indicative of superior respiratory function, directly correlate with enhanced athletic abilities (Mackała et al, 2019;Kurtoğlu et al, 2024;Lydia & Latha, 2019). Furthermore, yoga has emerged as a promising avenue for improving PFR and overall lung function.…”
Section: Introductionmentioning
confidence: 99%